PEMBERDAYAAN UMKM DESA AFDELING 1 RANTAUPRAPAT MELALUI PEMASARAN DIGITAL, KEMASAN, DAN INOVASI PRODUK - Munthe, Ibnu Rasyid; Fitriandika Sari, Novi; Helvi Rambe, Bhakti; Gulo, Nur'ainun; Trya Amanda, Ade; Rasyid Munthe, Shabrina (Fakultas Teknik, Universitas Samudra, 2025)
The community service activity conducted in Afdeling 1 Village, Rantau Prapat, aimed to enhance the capacity of Micro, Small, and Medium Enterprises (UMKM) through training in three important aspects: digital marketing, packaging design, and product innovation. The main problems faced by local UMKM included marketing limited to the local market, unattractive product packaging, and a lack of product innovation. The methods used in this activity included training on the use of social media and e-commerce platforms for digital marketing, training on attractive and professional packaging design, and the development of new product variations to increase competitiveness. The results of the activity showed a significant increase, with 90% of UMKM actors now utilizing digital marketing, 80% of products experiencing improved packaging design, and 75% of UMKM actors successfully developing new products. The positive impacts of this activity included increased UMKM income, expanded market reach, and increased consumer confidence in the products offered. Overall, this activity successfully empowered UMKM to compete better in a wider market and contributed to local economic empowerment in Afdeling 1 Village, Rantau Prapat. The sustainability of this program requires further mentoring and support from various parties so that UMKM can continue to grow and be competitive